Play interventions for paediatric patients in hospital: a scoping review. Issue 7 (26th July 2021) - Gjærde, Line Klingen; Hybschmann, Jane; Dybdal, Daniel; Topperzer, Martha Krogh; Schrøder, Morten Arnborg; Gibson, Jenny Louise; Ramchandani, Paul; Ginsberg, Elisabeth Ida; Ottesen, Bent; Frandsen, Thomas Leth; Sørensen, Jette Led
Abstract : Objective: Play is a non-invasive, safe and inexpensive intervention that can help paediatric patients and their families manage difficult aspects of being ill or hospitalised. Although play has existed in hospitals for decades, research on hospital play interventions is scarce. This review aimed to categorise and synthesise the last 20 years of research on hospital play interventions. Design: Scoping review. Data sources: PubMed, CINAHL, CENTRAL, ERIC and PsycINFO (1 January 2000– 9 September 2020). Study selection and data extraction: We systematically searched for original peer-reviewed articles, written in English, on hospital play interventions in paediatric patients (0–18 years) in non-psychiatric settings. Two reviewers independently screened titles and abstracts, reviewed full text of relevant articles and extracted data. We thematically synthesised the data from the included studies, and a descriptive analysis, based on a developed framework, is presented. Results: Of the 297 included articles, 78% came from high-income countries and 56% were published within the last 5 years. Play interventions were carried out across all ages by various healthcare professionals. Play interventions served different roles within four clinical contexts: A) procedures and diagnostic tests, B) patient education, C) treatment and recovery and D) adaptation. Across these contexts, play interventions were generally facilitated and purpose-oriented and had positive reported effects on pain, stress, and anxiety. Conclusions: Play in hospitals is an emerging interdisciplinary research area with a significant potential benefit for child and family health. Future research should further describe principles for play in hospitals. High-quality studies investigating short-term and long-term effects are needed to guide when and how to best integrate play in hospitals.